Refractory Hyperammonemic encephalopathy in Fibrolamellar hepatocellular carcinoma, a case report and literature review - Arwa Ahmed (17563305) (2022)
Fibrolamellar hepatocellular carcinoma is a rare type of hepatocellular carcinoma with unclear etiology. Its prevalence ranges from 0.6%-5%. One of the rare manifestations of FHCC includes hyperammonemic hepatic encephalopathy (HAE). Data regarding HAE in FHCC is limited to case reports, and much is unknown, including its precipitating factors, clinical course, and management. We have reported one such case of FHCC associated HAE and presented an extensive literature review on the topic. We report the case of a 26-year-old Pakistani male who was diagnosed with fibrolamellar hepatocellular carcinoma. On day five after the first chemotherapy, he presented with nausea, vomiting, and confusion. His serum ammonia level was raised, and he was treated with lactulose and rifaximin. The patient continued chemotherapy and had recurrent admissions with HAE. A detailed workup revealed acquired ornithine transcarbamylase deficiency. Ammonia level peaked at 694 umol/L during the clinical course of his disease. He received treatment with multiple ammonia scavengers, including sodium benzoate + phenylacetate, with relief of symptoms and reduction in ammonia level. The patient was eventually lost to follow-up. HAE presents as a paraneoplastic manifestation of FHCC. Patients have laboratory features suggestive of acquired ornithine transcarbamylase deficiency. There is a variable frequency of episodes reported in the literature. Most patients respond well to ammonia scavenger therapies rather than conventional HE management with lactulose or rifaxmin. Other Information Published in: Current Problems in Cancer License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.currproblcancer.2022.100847